Adoption of Online Resources to Improve the Marketing Performance of SMEs - Aunj Kumar; Asif Ali Syed; Anoop Pandey (ACHSM, 2021)
With the increase in the pace of globalization, SMEs are facing stiff competition from multinational firms. The entrepreneurs owning SMEs have fewer funds, but they need to improve the output of their organizations. Technology adoption can help owners of SMEs to match up with the pace of multinational firms because it can increase their reach and improve overall performance. In this paper, the authors will discuss whether online resource adoption (social media, e-commerce, technology 4.0) will enhance the marketing standard of small and medium enterprises or not. SMEs can achieve economies of scale because of the prominent usage of technology. The findings of this paper will help owners/managers of Indian SMEs to understand the use of online resources in improving marketing within a limited budget. COVID-19 has also pushed all the organizations towards the usage of technology. Either big or small organizations, none of them can ignore the use of technical sources for marketing in this digital era.